AB033. Preimplantation genetic diagnosis of spinal muscular atrophy in Vietnam - Khoa, Tran Van (Ann Transl Med, 2015)
OBJECTIVE: Spinal muscular atrophy (SMA) is a severe neurodegenerative autosomal recessive disorder. Most of patients are caused by the homozygous absence of exon 7 of the telomeric copy of the SMN gene (SMNt) on chromosome 5. Setting up a molecular diagnostic protocol for detecting exon 7 gen SMNT homozygous deletion in single cell is basic to preimplantation genetic diagnosis of spinal muscular atrophy. METHODS: This study was carried out on 17 patients and their parents. Firstly, lymphocytes of patients and their parents were isolated from fresh blood by ficoll. Taking a lymphocyte on stereoscopic microscope, lysing the cell, amplifying whole genome, then amplifying exon 7 of SMNT gene by using a polymerase chain reaction, followed by HinfI restriction digest enzyme of the PCR enabling the important SMNT gene to be distinguished from the centromic SMN gene (SMNc) which has no clinical phenotype to detect mutation. Electrophoresis PCR products after digesting by restriction enzyme and analysis. Besides, the minisequencing technique has also been used to detect the absence of exon 7 of SMNT gene based on the difference of one nucleotide at 214-position in exon 7 (C-SMNT, T-SMNc). Secondly, the application of the protocol was set up on one lymphocyte to preimplantation genetic diagnosis of spinal muscular atrophy on biopsied blastomeres. RESULTS: Two different protocols which were PCR-RFLP and minisequencing, were set up on 200 lymphocytes from 17 patients and their parents to screen the homozygous deletion in exon 7 SMNT gene with the PCR efficiency in 96%. The results were similar with the gene diagnosed from fresh blood. The methods were also efficient, providing interpretable result in 96.55% (28/29) of the blastomeres tested. Three couples were treated using this method. Three normal embryos were transfer which resulted in one clinical pregnancy. CONCLUSIONS: We have successfully applied the technique of PCR-RFLP and minisequencing for the preimplantation genetic diagnosis of spinal muscular atrophy.